Laboratory Investigation of Materials Type Effects on the Microsurfacing Mixture - Shafaghat Lonbar, Mohammad; Nazirizad, Mahmoud (Civil Engineering Journal, 2016)
Pavement preservation is a quintessential system of treating pavements at the optimum time to maximize their useful life. One of the preventive maintenance treatment options is using microsurfacing system as the acceptable and economical solution. This study presents a laboratory investigation of aggregate type and adhesive materials and their relationship to microsurfacing pavement properties such as cohesion, wet track abrasion loss, excess asphalt and compaction. The method of this study relies on ISSA A143, using the Cohesion 30 min and 60 min, Wet track abrasion loss, Loaded-wheel excess asphalt and finally Loaded-wheel compaction. The verification of this method was achieved through measuring the various factors of specimens constructed in laboratory using two different aggregate sources as river and mountain aggregates and two binders as CSS-1h and CQS-1h. The results showed that mixes contain riverine aggregates showed more cohesion properties. Base on wet track test results mixes, mixes containing riverine type aggregate were more resistant to abrasion. In addition CQS-1h emulsion showed better adhesiveness against abrasion in both types of aggregates in asphalt mixes. With increased amount of emulsions in mixes, load wheel values increased as well. Loaded wheel compaction test results confirmed that river based aggregates are more susceptible to rutting failure. The results of wheel tracking test illustrated that CSS-1h emulsion applied in mixes had better resistance to rutting.